THE EFFECT OF PROMOTION ON PURCHASE DECISIONS MEDIED ​​BY CONSUMER BUYING INTEREST IN SMALL MEDIUM BUSINESS BANANA AND ONION CHIPS IN RENGAT DISTRICT - Roky Apriansyah; Hermanto Hermanto; Yusnedi Yusnedi; Warnadi Warnadi; Suwaji Suwaji (LPPM Press STIE Indragiri Rengat, 2022)
This research was conducted on Small and Medium Enterprises in Rengat District. The purpose of this study was to determine the effect of promotion on purchasing decisions mediated by buying interest in Small and Medium Enterprises in Rengat District. With the number of samples used as many as 98 respondents. Data processing using IBM SPSS Statistic 21 program. The results of this study indicate that: (1) Promotion has a positive effect on Purchase Interest. (2) Promotion has a positive effect on purchasing decisions. (3) Purchase intention has a positive effect on purchasing decisions. (4) Promotion has an effect on purchasing decisions mediated by buying interest.